Stability of microprocessor relay protection and automation systems against intentional destructive electromagnetic impacts. Part 2 - Gurevich, V. I. (НТУ "ХПИ", 2011)
Problems of impact of the electromagnetic high-power pulses generated at nuclear explosion or by means of the special equipment, intended specially for damage of the electronic equipment, in particular digital protective relays and automatic systems, and also ways of protection from these impacts are considered.

В статье рассматриваются проблемы воздействия мощных электромагнитных импульсов, генерируемых при ядерном взрыве или с помощью специального оборудования, предназначенных специально для повреждения электронной аппаратуры, в частности микропроцессорных устройств релейной защиты и автоматики, а также меры защиты от этих воздействий.
Keywords: electronic equipment; relay protection; electromagnetic impacts; ядерный взрыв; микропроцессорные устройства; релейная защита; автоматика; электромагнитные импульсы